2018
DOI: 10.3390/cryst8010052
|View full text |Cite
|
Sign up to set email alerts
|

Crystal Chemistry of Zinc Quinaldinate Complexes with Pyridine-Based Ligands

Abstract: Substitution of methanol in [Zn(quin) 2 (CH 3 OH) 2 ] (quin − denotes an anionic form of quinoline-2-carboxylic acid, also known as quinaldinic acid) with pyridine (Py) or its substituted derivatives, 3,5-lutidine (3,5-Lut), nicotinamide (Nia), 3-hydroxypyridine (3-Py-OH), 3-hydroxymethylpyridine (3-Hmpy), 4-hydroxypyridine (4-Py-OH) and 4-hydroxymethylpyridine (4-Hmpy), afforded a series of novel heteroleptic complexes with compositions [Zn(quin) (6) (4-Pyridone = a keto tautomer of 4-hydroxypyridine), and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 66 publications
0
6
0
Order By: Relevance
“…10. In the monoclinic polymorph, four N-H(pyroH + )/COO À contacts with lengths not longer than 2.776(4)Å link two [Zn(quin) 3 ] À ions with two pyrrolidinium cations into a cyclic motif, denoted as R 4 4 (20). In the triclinic polymorph, one N-H/COO À contact is longer, it amounts to 2.926(3)Å.…”
Section: Intermolecular Interactionsmentioning
confidence: 99%
See 1 more Smart Citation
“…10. In the monoclinic polymorph, four N-H(pyroH + )/COO À contacts with lengths not longer than 2.776(4)Å link two [Zn(quin) 3 ] À ions with two pyrrolidinium cations into a cyclic motif, denoted as R 4 4 (20). In the triclinic polymorph, one N-H/COO À contact is longer, it amounts to 2.926(3)Å.…”
Section: Intermolecular Interactionsmentioning
confidence: 99%
“…Surprisingly, a search of the Cambridge Structural Database (CSD) has revealed that its zinc(II) complexes are fairly scarce. 14 There are reports of zinc(II) quinaldinate complexes with water, 13 methanol, 15 dimethylsulphoxide, 16 imidazole, 17 1-methylimidazole, 18 a tridentate N,N,S ligand, 19 pyridine-based ligands 20 and recently also amino alcohols. 21 The latter two systems are results of our previous work.…”
Section: Introductionmentioning
confidence: 99%
“…Based on the previous study of related zinc(II) complexes with quinaldinate [36], [Cu(quin) 2 (H 2 O)] was expected to undergo a straightforward substitution of water with the amine ligand. At fairly mild conditions, the displacement reactions should result in complexes with one or two amine ligands, [Cu(quin) 2 (amine)] and [Cu(quin) 2 (amine) 2 ].…”
Section: Synthetic Considerationsmentioning
confidence: 99%
“…These three atoms may react as electron-donating during the coordination binding with Zn 2+ . However, as [74] mentioned since Zn 2+ does not behave reliably either as a soft or as a hard Lewis acid, it poses a borderline case with no particular fondness for oxygen, nitrogen or sulfur-donor ligands to be coordinated, the results of the concluded binding coordination sites to form complexes were differ. Roughly, we reviewed all of them as there were no fixed preferences and the differ based on derivative, atoms presenting, molecular geometry, medium, and environment.…”
Section: Binding Studies Of 8-amidoquinoline Probes Via Solution Workmentioning
confidence: 99%